2019
DOI: 10.2147/cmar.s226264
|View full text |Cite
|
Sign up to set email alerts
|

<p>Upregulation Of circMMP9 Promotes Osteosarcoma Progression Via Targeting miR-1265/CHI3L1 Axis</p>

Abstract: BackgroundOsteosarcoma (OS) is a very aggressive cancer. Nevertheless, how circular RNA (circRNA) contributes to OS progression remains unclear. Here, we aimed to research the functions of circMMP9 in OS progression.MethodsGene expression was determined via qRT-PCR. siRNA was used to knock down circMMP9. Proliferation was analyzed using CCK8 and colony formation assays. Migration and invasion were measured using Transwell assay.ResultscircMMP9 was overexpressed in cancer tissues. Overexpressed circMMP9 was cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Emerging studies have shown that circRNAs play a crucial role in regulating cell growth, cell cycle, cell apoptosis, cell migration, and cell metabolism in a series of cancer types, including OS [12]. For example, Pan et al found that circMMP9 promotes OS progression via targeting the miR-1265/CHI3L1 axis [13]. Zheng et al found that circRNA LRP6 induced OS development via negatively regulating KLF2 expression [14].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies have shown that circRNAs play a crucial role in regulating cell growth, cell cycle, cell apoptosis, cell migration, and cell metabolism in a series of cancer types, including OS [12]. For example, Pan et al found that circMMP9 promotes OS progression via targeting the miR-1265/CHI3L1 axis [13]. Zheng et al found that circRNA LRP6 induced OS development via negatively regulating KLF2 expression [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hsa_circ0021347 also showed the same prognostic trend (75). In contrast, research performed by Pan et al (34) suggested that overexpression of circMMP9 was correlated with advanced tumor stage and predicted a low survival rate by KM analysis. Circ_0102049 was remarkably correlated with patients' poor OS analyzed by KM curves in a study of 76 OSA patients (35).…”
Section: Circrna and Osteosarcoma Prognosismentioning
confidence: 84%
“…The circRNA-miRNA-mRNA network has been reported to involve in the mediation of tumorigenesis. 28 Some circRNAs can regulate gene expression via functioning as miRNA sponges. 23 For example, circGRAMD1B sponges miR-130a-3p to inhibit gastric cancer tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%